2006
DOI: 10.1093/rpd/ncl122
|View full text |Cite
|
Sign up to set email alerts
|

Development of LiF:Mg,Cu,Si TL material (new KLT-300) with a low-residual signal and high-thermal stability

Abstract: LiF-based thermoluminescence (TL) materials have been widely used for radiation dosimetry due to their attractive features. LiF:Mg,Cu,P is one of the most sensitive tissue-equivalent TL materials, approximately 40 times more sensitive than LiF:Mg,Ti (TLD-100), but it has two main drawbacks: a thermal loss of the TL sensitivity when annealed at temperatures>240 degrees C, and a relatively high-residual signal. Recently, LiF:Mg,Cu,Na,Si TL material was developed to overcome these drawbacks at the Korea Atomic En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Subsequently, Lee et al [77][78][79] reported dosimetric characteristics of a new LiF:Mg,Cu,Si thermoluminescent (TL) material developed at KAERI, Korea and compared with those of commercially available LiF:Mg,Cu,P (GR-200A)(China). It is reported that LiF:Mg,Cu,Si thermoluminescence dosimeter (TLD) can be heated up to 573 K without any loss of TL sensitivity or any change in the glow curve structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Lee et al [77][78][79] reported dosimetric characteristics of a new LiF:Mg,Cu,Si thermoluminescent (TL) material developed at KAERI, Korea and compared with those of commercially available LiF:Mg,Cu,P (GR-200A)(China). It is reported that LiF:Mg,Cu,Si thermoluminescence dosimeter (TLD) can be heated up to 573 K without any loss of TL sensitivity or any change in the glow curve structure.…”
mentioning
confidence: 99%
“…et al[60,61], Wu et al[62], DeWerd et al[95], Bhatt et al[27,96], Wang et al[63,64], Driscoll et al[ 52], Prokic and Botter-Jensen[23], Zha et al[24], Pradhan and Bhatt[97], Mahajna et al[85], Bilski et al[87,89], etc.. LiF:Mg,Cu,Na,Si and LiF:Mg,Cu,Si TL phosphors have been characterised by Nam et al[72], Jung et al[73], Lee et al[74], Tang et al[75,76], Lee et al[78,79], Kim et al[25], Rahman et al[80] and Tang et al[82,83].…”
mentioning
confidence: 99%
“…Annealing temperature and time are used to produce the lowest intrinsic background and to obtain the highest efficiency [7]. The details of the preparation procedure can be found elsewhere [8].…”
Section: Sample Preparationmentioning
confidence: 99%